MECHANISMS AND CLINICAL PERSPECTIVES OF ALLERGEN-SPECIFIC IMMUNOTHERAPY - Leila Akhvlediani; Marina Izmailovich; Meruyert Gazaliyeva; Anna Skvortsova; Kanan Tanriverdiev (Interdisciplinary Approaches to Medicine)
Introduction: Allergic rhinitis (AR) is a prevalent condition in Kazakhstan, characterized by high sensitization to weed pollens, particularly Artemisia, with sensitization levels significantly exceeding those observed in Europe. AR often leads to complications such as bronchial asthma (BA) and other respiratory conditions. The "unified airways" concept emphasizes the interconnected nature of upper and lower airway inflammation, with ASIT showing promise in mitigating these effects.